2016
DOI: 10.1108/ijge-03-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Women’s entrepreneurship in Iran

Abstract: Purpose The purpose of this paper is to identify the growth motivations of women owning and managing home-based businesses (HBBs) in Iran. Design/methodology/approach The qualitative approach was used by 20 in-depth interviews with Iranian female HBBs owners/mangers. Findings The business growth motivations of women owning and managing HBBs were categorized in intrinsic and extrinsic motivations. Results show that women owning and managing HBBs are motivated to growth their businesses by intrinsic motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…The negative roles of husbands in women's businesses are also illustrated in the empirical evidence of some studies (Alexandre & Kharabsheh, 2019;Franck, 2012;Isaga, 2019;Lindvert et al, 2017;Salia et al, 2018). In highly patriarchal countries, one particularly critical issue for husbands is when their socially prescribed superior position as the breadwinner is perceived to be threatened by the income of women (Amine & Staub, 2009;Modarresi et al, 2016;Salia et al, 2018). In Iran, for example, husbands have been shown to take decision-making power, and to use other mechanisms of control over the businesses of women in order to uphold their self-identity and to maintain their control over the family (Modarresi et al, 2016).…”
Section: The Role Of Husbandsmentioning
confidence: 99%
“…The negative roles of husbands in women's businesses are also illustrated in the empirical evidence of some studies (Alexandre & Kharabsheh, 2019;Franck, 2012;Isaga, 2019;Lindvert et al, 2017;Salia et al, 2018). In highly patriarchal countries, one particularly critical issue for husbands is when their socially prescribed superior position as the breadwinner is perceived to be threatened by the income of women (Amine & Staub, 2009;Modarresi et al, 2016;Salia et al, 2018). In Iran, for example, husbands have been shown to take decision-making power, and to use other mechanisms of control over the businesses of women in order to uphold their self-identity and to maintain their control over the family (Modarresi et al, 2016).…”
Section: The Role Of Husbandsmentioning
confidence: 99%
“…The inherent attitudes of a patriarchal society, that men are superior to women and that women are best suited to play the reproductive roles, pose significant challenges for these Malay Muslim women entrepreneurs. With the exception of few studies in the Middle East (Shmiln 2017;Modarresi et al 2016;Studholme 2013), the study on patriarchal constraints impacting on Muslim women entrepreneurs particularly in the South East Asian region is scarce. By using a gender lens and the bargaining patriarchy conceptual framework, this article will explore how Malay Muslim women entrepreneurs negotiate their patriarchal constraints that have a significant impact on their business sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the literature is relatively scarce on the relationship between the need for achievement, an actual entrepreneurial venture and the subsequent entrepreneurial performance among women entrepreneurs. Modarresi et al (2016) found that the need for achievement is one of their primary motivations for business growth. Similarly, Khan et al (2021) reported that the need for achievement is a positive predictor of an entrepreneur's success.…”
Section: Theoretical Foundations and Hypotheses Developmentmentioning
confidence: 99%